OPTIMALISASI PROGRAM REMEDIAL BERDASARKAN INSTRUMEN AKREDITASI SATUAN PENDIDIKAN DALAM PEMBELAJARAN DIFERENSIASI KURIKULUM MERDEKA - Rosyida, Nadya Ilma; Nugraha, Sri Wisnu; Agustin, Usman; Rochman, Chaerul; Nuryantini, Ade Yeti (Jurnal Evaluasi Pendidikan, 2023)
This study aims to qualitatively examine the optimization of remedial programs in differentiation learning in the Independent Curriculum based on the 2020 Education Unit Accreditation Instrument. This research is a literature study that discusses implementing differentiated remedial programs. This research originates from articles related to remedial programs in differentiation learning and IASP 2020 instrument remedial program items from books, research articles, and other supporting sources. The remedial program is carried out to improve the teacher's ongoing learning. The results of the studies that have been carried out show that the independent curriculum differentiation learning remedial program is appropriate to be implemented to optimize learning because the timing of this remedial program is more flexible; it does not have to be carried out at the end. Based on point 14 in the 2020 Education Unit Accreditation Instrument regarding the learning process, this remedial program can be measured using the indicators in the 2020 Education Unit Accreditation Instrument. This study aims to qualitatively examine the optimization of remedial programs in differentiation learning in the Independent Curriculum based on the Education Unit Accreditation Instrument 2020.